Comparative behaviour of hollow-reinforced concrete column strengthened with carbon fibre-reinforced polymer and shape memory alloy - Ismail, Ruqayyah (2019)
In construction industry, circular hollow reinforced concrete column is commonly being utilized for its capacity in reducing its mass and ability to provide more moment resistance. However, through time circular hollow reinforced concrete column (CHRCC), strengthening or retrofitting work is required due to poor construction quality, natural disaster and others. Replacing deteriorated structure with a new one will cost fortune compared to strengthening or retrofitting work. Therefore, this study investigates the behaviour of CHRCC strengthened with carbon fibre reinforced polymer (CFRP) and shape memory alloy (SMA). Besides CFRP, this study is using shape memory alloy (SMA) as strengthening material. This study is divided into two stages, first stage is testing concrete cylinder with CFRP and SMA partial confinement while the second stage is testing circular hollow reinforced concrete column with CFRP and SMA partial confinement. In the first stage of this study, comparison study between the full and partial CFRP confinement were made. By using concrete cylinder specimen, confinement mechanism to be used for circular hollow reinforced concrete column (2nd stage) was determined. For second stage of the experimental work, focus is more on to investigate the behaviour of circular hollow reinforced concrete column under axial and eccentric loading. From the experimental work, it has concluded that, partial CFRP confinement with horizontal strip with spacing 20 mm able to perform efficiently with only 1.04 % ultimate compressive strength lower than full CFRP confinement. As CHRCC with partial CFRP confinement, this study has concluded that the ultimate compressive strength increased significantly as well. Comparison with other sustainable material, Shape Memory Alloy (SMA) in this study, has proven that with lesser SMA strips, CHRCC experienced 20% load increment compared to unconfined CHRCC. A comparison of the model analysis in ABAQUS was made with the experimental results which showed good agreement of the data validation.